"Handle with care": The mediating role of schedule i‐deals in the relationship between supervisors' own caregiving responsibilities and employee outcomes. (July 2017) - Las Heras, Mireia; Van der Heijden, Beatrice I.J.M.; De Jong, Jeroen; Rofcanin, Yasin
Abstract: Drawing on theories of perspective‐taking and i‐deals, this study explores the impact of supervisors' own caregiving responsibilities for elders and parental status on subordinates' schedule i‐deals. Moreover, we investigate the extent to which schedule i‐deals mediate the relationship between supervisors' caregiving responsibilities and two employee outcomes: satisfaction with work–family balance and turnover intentions. Using a sample of 520 dyads involving 137 supervisors and 520 employees, the results of multilevel analysis show that supervisors' caregiving responsibilities for elders is positively related to schedule i‐deals, but their parental status is not. The findings also show that schedule i‐deals mediate the effect of supervisors' caregiving responsibilities for elders on subordinates' satisfaction with work–family balance and turnover intentions. This research contributes to the i‐deals' literature by focusing on the role of managers' own caregiving responsibilities in facilitating the provision of schedule i‐deals to their subordinates and by exploring the consequences of schedule i‐deals to gain an understanding of the mutually beneficial nature of such deals. From a practical point of view, supervisors and HR departments might utilise schedule i‐deals to drive desirable employee outcomes, in particular their caregiving responsibilities, and to engender a family‐supportive organisational culture.